THE INFLUENCE OF TOURIST EXPERIENCE ON REVISIT INTENTION: THE MEDIATING ROLE OF SATISFACTION AMONG GENERATION Z IN LABUAN BAJO - Panca, Gusti; Wihardi, Doddy (Bajang Institute, 2025)
This study examines the significant influence of tourist experiences on revisit intentions and satisfaction, with a focus on Labuan Bajo, Indonesia, and Generation Z tourists. Based on data from 386 respondents, the study employs Structural Equation Modeling (SEM) using Partial Least Squares (PLS) to analyze the direct and indirect effects. The findings reveal that a positive tourist experience directly influences both revisit intentions and satisfaction, with satisfaction mediating the relationship between experience and revisit intentions. The results align with previous research, emphasizing that when expectations are met or exceeded, tourists are more likely to return and recommend the destination. For Labuan Bajo, catering to Generation Z's preferences for authentic, shareable experiences can enhance satisfaction and ensure the destination's long-term sustainability. The SEM-PLS analysis provides valuable insights for destination managers seeking to improve tourist experiences and increase repeat visits